Nickel-zinc ferrite material as well as preparation method and application thereof

By optimizing the ratio of nickel -zinc and zinc oxygen material and adding auxiliary components, the problem of low magnetic guidance rate and insufficient temperature of the existing materials within the wide temperature range, and the high initial magnetic conduct rate, low temperature coefficient and low temperature coefficient and The comprehensive performance of high temperature temperature is suitable for aviation electronics, automotive electronics and communication electronics.

CN119371197APending Publication Date: 2025-01-28HENGDIAN GRP DMEGC MAGNETICS CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310938574.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-27
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing nickel-zinc ferrite materials have low magnetic permeability in a wide temperature range and insufficient Curie temperature, resulting in poor output stability under extremely low temperature/high temperature conditions and high preparation costs.

Method used

By optimizing the types and contents and contents of nickel-zinc and zinc oxygen materials, the types and contents and contents of the auxiliary components of the nickel-zinc body material are prepared, and the NIO, 16.5-18.4WT%of the FE2O3, 8.5-10.5WT%of 63.6-66.7WT%, are prepared. WT%of CUO materials, and add 600-3000ppm BI2O3, 1500-2500PPM's CO2O3 and 30-80ppm nano SiO2, forming materials with high initial magnetic guidance and low temperature coefficients.

Benefits of technology

In the wide temperature range of -40 to 140 ° C, the material has high initial magnetic guidance and low temperature coefficients. The Curie temperature TC reaches 200 ° C or more. The comprehensive performance is excellent. Sex and reduce preparation costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371197A_ABST
    Figure CN119371197A_ABST
Patent Text Reader

Abstract

The invention provides a nickel-zinc ferrite material as well as a preparation method and application thereof. The nickel-zinc ferrite material is prepared from main components and auxiliary components, according to the total weight of the main components, the main components comprise the following components in percentage by weight: 63.6 to 66.7 percent of Fe2O3, 8.5 to 10.5 percent of NiO, 16.5 to 18.4 percent of ZnO and 7.6 to 8.5 percent of CuO; according to the total weight of the main components, the auxiliary components comprise the following components in parts by weight: 600 to 3000 ppm of Bi2O3, 1500 to 2500 ppm of Co2O3 and 30 to 80 ppm of nano SiO2. The nickel-zinc ferrite material provided by the invention has wide temperature performance, high magnetic conductivity and high Curie temperature, the stability of the material is improved, the service life of the material is prolonged, meanwhile, the preparation cost is reduced, and large-scale popularization and application are facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of soft ferrite materials, and relates to a nickel-zinc ferrite material, and in particular to a nickel-zinc ferrite material and a preparation method and application thereof. Background Art

[0002] In recent years, ferrite materials have been increasingly widely used in various industries such as communications, IT, automobiles, aerospace, ships, and defense weapon systems, and surface mount components must meet conditions such as being suitable for surface mounting and welding and having good strength. As surface mount components continue to develop in the direction of miniaturization and thinness, the ferrite market has put forward higher requirements for the thermal shock resistance and electromagnetic properties of NiZn materials.

[0003] Outdoor facilities, satellites and other devices of modern communication equipment, whether in hot tropical areas or cold frigid areas, are not only required to withstand high temperatures, but also severe cold. This requires the components used to have excellent characteristics such as wide temperature range, high magnetic permeability, high stability and long life.

[0004] At present, the wide temperature and high magnetic permeability of soft magnetic nickel-zinc ferrite materials on the market are generally below 300, and the magnetic core is generally made of MnZn ferrite material. Inductors made of this material are prone to cracking during tinning, which leads to the disadvantages of low energy conversion efficiency and limited operating temperature in products made of NiZn materials during use.

[0005] CN101169996A discloses a low-power Mn-Zn ferrite magnetic material for use under ultra-high temperature conditions and a preparation method thereof. The invention adds numerous impurities such as ZrO2, CaCO3, Nb2O5 and Co2O3 to the main components of ferrite Fe2O3, NiO, ZnO and CuO at the same time, thereby achieving the effects of high Bs and high Tc. However, its magnetic permeability after sintering is low, and the performance of the above-mentioned materials at low temperatures is not involved.

[0006] CN112079633A discloses a nickel-zinc high magnetic permeability material with a wide temperature range and a low specific temperature coefficient and a preparation method thereof, wherein the nickel-zinc high magnetic permeability material comprises a main component and an auxiliary component, wherein the main component contains 47-49.8 mol% of Fe2O3, 11.6-15.6 mol% of NiO and 30-34.5 mol% of ZnO, and the remainder is CuO, calculated based on the total amount of Fe2O3, ZnO, NiO and CuO; the content of the auxiliary component is based on the total weight of the main component, and comprises 0.01-0.3 wt% of Co2O3, 0.05-0.25 wt% of SnO2 and 0.03-0.4 wt% of Bi2O3. The above material has the advantages of high magnetic permeability and high Bs, but its sintering temperature is high, and the purpose of cost reduction cannot be achieved, and its Curie temperature is low, and it cannot be used to make magnetic bead inductors.

[0007] CN110357610A discloses a nickel-zinc ferrite material and its preparation method and use. The invention adds a number of trace elements such as ZrO2, CaCO3, Nb2O5 and Co2O3 to the main components of ferrite Fe2O3, Ni2O3, ZnO and CuO, achieving the effect of high magnetic permeability and high temperature impact resistance. Although the invention solves the problem that traditional power materials cannot meet the requirements of automotive electronic products, the wide temperature performance of the above materials does not meet the required requirements.

[0008] It can be seen that how to provide a nickel-zinc ferrite material and a preparation method thereof, taking into account wide temperature performance, high magnetic permeability and high Curie temperature, improving material stability, extending its service life, and reducing preparation costs, has become an urgent problem that technical personnel in this field need to solve. Summary of the invention

[0009] The purpose of the present invention is to provide a nickel-zinc ferrite material and a preparation method and application thereof. The nickel-zinc ferrite material has wide temperature performance, high magnetic permeability and high Curie temperature, improves material stability, prolongs its service life, and reduces preparation costs, which is conducive to large-scale promotion and application.

[0010] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0011] In a first aspect, the present invention provides a nickel-zinc ferrite material, wherein the nickel-zinc ferrite material is made of a main component and an auxiliary component.

[0012] Based on the total weight of the main components, the main components include: 63.6-66.7wt% Fe2O3, 8.5-10.5wt% NiO, 16.5-18.4wt% ZnO and 7.6-8.5wt% CuO.

[0013] Calculated by the total weight of the main components, the auxiliary components include: 600-3000 ppm of Bi2O3, 1500-2500 ppm of Co2O3 and 30-80 ppm of nano-SiO2.

[0014] In the present invention, the average particle size of the nano-SiO2 is 100-200nm, for example, it can be 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm or 200nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0015] The present invention optimizes and controls the ratio of main components and the types and contents of auxiliary components on the basis of traditional nickel-zinc ferrite materials. The obtained nickel-zinc ferrite material has high initial magnetic permeability and low temperature coefficient in a wide temperature range of -40 to 140°C, and the Curie temperature Tc is above 200°C. The comprehensive performance is excellent, and the problem of low magnetic permeability of the material under different conditions is solved, thereby improving the output stability of the inductor under extremely low temperature / high temperature conditions. The inductor can be widely used in the fields of avionics, automotive electronics, communication electronics, etc.

[0016] In the present invention, the proportion of Fe2O3 is 63.6-66.7wt%, for example, it can be 63.6wt%, 63.8wt%, 64wt%, 64.5wt%, 65wt%, 65.5wt%, 66wt%, 66.5wt% or 66.7wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0017] In the present invention, the proportion of NiO is 8.5-10.5wt%, for example, it can be 8.5wt%, 8.6wt%, 8.8wt%, 9wt%, 9.2wt%, 9.4wt%, 9.6wt%, 9.8wt%, 10wt%, 10.2wt%, 10.4wt% or 10.5wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0018] In the present invention, the proportion of ZnO is 16.5-18.4wt%, for example, it can be 16.5wt%, 16.6wt%, 16.8wt%, 17wt%, 17.2wt%, 17.4wt%, 17.6wt%, 17.8wt%, 18wt%, 18.2wt% or 18.4wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0019] In the present invention, the proportion of CuO is 7.6-8.5wt%, for example, it can be 7.6wt%, 7.7wt%, 7.8wt%, 7.9wt%, 8wt%, 8.1wt%, 8.2wt%, 8.3wt%, 8.4wt% or 8.5wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0020] In the present invention, the proportion of Bi2O3 is 600-3000ppm, for example, it can be 600ppm, 800ppm, 1000ppm, 1200ppm, 1400ppm, 1600ppm, 1800ppm, 2000ppm, 2200ppm, 2400ppm, 2600ppm, 2800ppm or 3000ppm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0021] In the present invention, the proportion of Co2O3 is 1500-2500ppm, for example, it can be 1500ppm, 1600ppm, 1700ppm, 1800ppm, 1900ppm, 2000ppm, 2100ppm, 2200ppm, 2300ppm, 2400ppm or 2500ppm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] In the present invention, the proportion of nano-SiO2 is 30-80ppm, for example, it can be 30ppm, 35ppm, 40ppm, 45ppm, 50ppm, 55ppm, 60ppm, 65ppm, 70ppm, 75ppm or 80ppm, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0023] In a second aspect, the present invention provides a method for preparing the nickel-zinc ferrite material as described in the first aspect, wherein the preparation method comprises batching, pre-sintering, ball milling, granulation, molding and sintering performed in sequence.

[0024] Preferably, the batching comprises: weighing the main components according to the weight ratio and sequentially performing wet ball milling and spray granulation.

[0025] Preferably, during the wet ball milling process, the mixing mass ratio of the main component, the grinding medium and the water is 1:(4-8):(0.5-1.2), for example, it can be 1:4:0.5, 1:5:0.8, 1:6:0.9, 1:7:1 or 1:8:1.2, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0026] Preferably, the wet ball milling time is 20-60 min, for example, it can be 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] Preferably, the particle size distribution of the slurry obtained by wet ball milling satisfies X50 of 0.5-1.2 μm, for example, it can be 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm or 1.2 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0028] Preferably, the particle size distribution of the slurry obtained by wet ball milling satisfies X90 of 1.5-2μm, for example, it can be 1.5μm, 1.55μm, 1.6μm, 1.65μm, 1.7μm, 1.75μm, 1.8μm, 1.85μm, 1.9μm, 1.95μm or 2μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0029] Preferably, the pre-firing is carried out in a rotary kiln.

[0030] Preferably, the pre-firing temperature is 780-950°C, for example, it can be 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C, 900°C, 910°C, 920°C, 930°C, 940°C or 950°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] Preferably, the pre-burning time is 2-4h, for example, it can be 2h, 2.2h, 2.4h, 2.6h, 2.8h, 3h, 3.2h, 3.4h, 3.6h, 3.8h or 4h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] Preferably, the ball milling includes: pouring the pre-burned main component into a ball mill, and adding auxiliary components, water, adhesive, dispersant and defoamer, and first performing low-speed ball milling and then high-speed ball milling during the feeding process; after the ball milling is completed, the slurry is transferred to a stirring tank.

[0033] In the present invention, the binder, dispersant and defoamer are all ball milling additives conventionally used in the art, as long as they can achieve the corresponding functions, so there is no particular limitation on the specific type of each additive. For example, the binder can be polyvinyl alcohol, polyvinyl butyral or hydroxymethyl cellulose, the dispersant can be ammonium citrate, polyacrylic acid or polyacrylamide, and the defoamer can be n-octanol, stearic acid or tributyl phosphate.

[0034] Preferably, the mixing mass ratio of the main component, water, adhesive, dispersant and defoamer is 100:(40-150):(4-20):(0.1-2):(0.001-0.0025), for example, it can be 100:40:4:0.1:0.001, 100:50:5:0.2:0.001, 100:60:6:0.4:0.001, 100:70:8:0.6:0.001, 100:80:10:0.8:0.001 , 100:90:12:1:0.002, 100:100:14:1.2:0.002, 100:110:15:1.4:0.002, 100:120:16:1.6:0.002, 100:130:17:1.8:0.002, 100:140:18:2:0.002 or 100:150:20:2:0.0025, but are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0035] Preferably, the rotation speed of the low-speed ball mill is 20-60 rpm, for example, it can be 20 rpm, 25 rpm, 30 rpm, 35 rpm, 40 rpm, 45 rpm, 50 rpm, 55 rpm or 60 rpm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] Preferably, the low-speed ball milling time is 5-10 min, for example, it can be 5 min, 5.5 min, 6 min, 6.5 min, 7 min, 7.5 min, 8 min, 8.5 min, 9 min, 9.5 min or 10 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] Preferably, the rotation speed of the high-speed ball mill is 240-360rpm, for example, it can be 240rpm, 250rpm, 260rpm, 270rpm, 280rpm, 290rpm, 300rpm, 310rpm, 320rpm, 330rpm, 340rpm, 350rpm or 360rpm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0038] Preferably, the high-speed ball milling time is 0.5-2h, for example, it can be 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0039] Preferably, the granulation comprises spray granulation.

[0040] Preferably, the average particle size of the particles obtained by spray granulation is 30-200 μm, for example, it can be 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm or 200 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0041] Preferably, the forming comprises press forming.

[0042] Preferably, the press molding obtains an annular blank with a size of H(20-30)mm×(10-20)mm×(8-12)mm, for example, it can be H20mm×10mm×8mm, H22mm×12mm×9mm, H24mm×14mm×10mm, H26mm×16mm×11mm, H28mm×18mm×12mm or H30mm×20mm×12mm, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0043] In the present invention, the size of the annular blank is H (20-30) mm × (10-20) mm × (8-12) mm, which specifically means that the outer diameter of the annular blank is 20-30 mm, the inner diameter is 10-20 mm, and the height is 8-12 mm.

[0044] Preferably, the density of the annular blank is 3.10-3.25 g / cm 3 , for example, it can be 3.10 g / cm 3 、3.11g / cm 3 、3.12g / cm 3 、3.13g / cm 3 、3.14g / cm 3 、3.15g / cm 3 、3.16g / cm 3 、3.17g / cm 3、3.18g / cm 3 、3.19g / cm 3 、3.20g / cm 3 、3.21g / cm 3 、3.22g / cm 3 、3.23g / cm 3 、3.24g / cm 3 or 3.25g / cm 3 , but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0045] Preferably, the sintering is carried out in a bell kiln.

[0046] Preferably, the sintering includes: heating to a first temperature at a first rate and keeping it at that temperature for a first time, heating to a second temperature at a second rate and keeping it at that temperature for a second time, cooling to a third temperature at a third rate, and finally cooling to a fourth temperature at a fourth rate in an air atmosphere.

[0047] Preferably, the first rate is 0.5-2.5℃ / min, for example, it can be 0.5℃ / min, 0.6℃ / min, 0.8℃ / min, 1℃ / min, 1.2℃ / min, 1.4℃ / min, 1.6℃ / min, 1.8℃ / min, 2℃ / min, 2.2℃ / min, 2.4℃ / min or 2.5℃ / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0048] Preferably, the first temperature is 550-750°C, for example, it can be 550°C, 560°C, 580°C, 600°C, 620°C, 640°C, 660°C, 680°C, 700°C, 720°C, 740°C or 750°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0049] Preferably, the first time is 2-7h, for example, it can be 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h or 7h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0050] Preferably, the second rate is 1-3°C / min, for example, it can be 1°C / min, 1.2°C / min, 1.4°C / min, 1.6°C / min, 1.8°C / min, 2°C / min, 2.2°C / min, 2.4°C / min, 2.6°C / min, 2.8°C / min or 3°C / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0051] Preferably, the second temperature is 850-1000°C, for example, it can be 850°C, 860°C, 880°C, 900°C, 920°C, 940°C, 960°C, 980°C or 1000°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0052] Preferably, the second time is 2-5 hours, for example, it can be 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours or 5 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0053] Preferably, the third rate is 4-7°C / min, for example, it can be 4°C / min, 4.5°C / min, 5°C / min, 5.5°C / min, 6°C / min, 6.5°C / min or 7°C / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0054] Preferably, the third temperature is 500-700°C, for example, it can be 500°C, 520°C, 540°C, 560°C, 580°C, 600°C, 620°C, 640°C, 660°C, 680°C or 700°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0055] Preferably, the fourth rate is 6-10℃ / min, for example, it can be 6℃ / min, 6.5℃ / min, 7℃ / min, 7.5℃ / min, 8℃ / min, 8.5℃ / min, 9℃ / min, 9.5℃ / min or 10℃ / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0056] Preferably, the fourth temperature is 40-60°C, for example, it can be 40°C, 42°C, 44°C, 46°C, 48°C, 50°C, 52°C, 54°C, 56°C, 58°C or 60°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0057] As a preferred technical solution of the second aspect of the present invention, the preparation method comprises the following steps:

[0058] (1) Preparation: Weigh the main components according to the weight ratio and perform wet ball milling and spray granulation in sequence; wherein, during the wet ball milling, the mixing mass ratio of the main component, the grinding medium and water is 1:(4-8):(0.5-1.2), the ball milling time is 20-60 min, and the particle size distribution of the obtained slurry satisfies X50 of 0.5-1.2 μm and X90 of 1.5-2 μm;

[0059] (2) Pre-burning: The material obtained by spray granulation is placed in a rotary kiln for pre-burning at a temperature of 780-950°C for 2-4 hours;

[0060] (3) ball milling: pour the pre-calcined main component into a ball mill, and add auxiliary components, water, adhesive, dispersant and defoamer, and the mixing mass ratio of the main component, water, adhesive, dispersant and defoamer is 100:(40-150):(4-20):(0.1-2):(0.001-0.0025); during the feeding process, first perform low-speed ball milling at 20-60rpm for 5-10min, and then perform high-speed ball milling at 240-360rpm for 0.5-2h; after the ball milling is completed, transfer the slurry to a stirring tank;

[0061] (4) Granulation: The slurry obtained by ball milling is sprayed and granulated into material particles with an average particle size of 30-200 μm in a spray tower;

[0062] (5) Molding: The material particles are pressed and molded to obtain a density of 3.10-3.25g / cm 3 H(20-30)mm×(10-20)mm×(8-12)mm annular blank;

[0063] (6) Sintering: Place the annular blank in a bell kiln, first heat it to 550-750°C at 0.5-2.5°C / min in an air atmosphere and keep it at that temperature for 2-7h, then heat it to 850-1000°C at 1-3°C / min and keep it at that temperature for 2-5h, then cool it to 500-700°C at 4-7°C / min, and finally cool it to 40-60°C at 6-10°C / min.

[0064] In a third aspect, the present invention provides an application of the nickel-zinc ferrite material as described in the first aspect, wherein the nickel-zinc ferrite material is used to prepare a broadband transformer, a filter inductor or a laminated magnetic bead for an electronic circuit.

[0065] Compared with the prior art, the present invention has the following beneficial effects:

[0066] The present invention optimizes and controls the ratio of main components and the types and contents of auxiliary components on the basis of traditional nickel-zinc ferrite materials. The obtained nickel-zinc ferrite material has high initial magnetic permeability and low temperature coefficient in a wide temperature range of -40 to 140°C, and the Curie temperature Tc is above 200°C. The comprehensive performance is excellent, and the problem of low magnetic permeability of the material under different conditions is solved, thereby improving the output stability of the inductor under extremely low temperature / high temperature conditions. The inductor can be widely used in the fields of avionics, automotive electronics, communication electronics, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0067] Figure 1 This is a SEM photograph of the sintered nickel-zinc ferrite material obtained in Example 1. DETAILED DESCRIPTION

[0068] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0069] Example 1

[0070] This embodiment provides a nickel-zinc ferrite material and a preparation method thereof, the preparation method comprising the following steps:

[0071] (1) Ingredients: The main components were weighed according to the components and weight ratios shown in Table 1 and wet ball milled and spray granulated in sequence; wherein, during the wet ball milling, the mixing mass ratio of the main component, the grinding medium (a steel ball with a diameter of 5 mm) and water was 1:6:1, the ball milling time was 40 min, and the particle size distribution of the obtained slurry satisfied X50 of 0.8 μm and X90 of 1.8 μm;

[0072] (2) Pre-calcination: The material obtained by spray granulation is fed into a rotary kiln at a rate of 150 kg / h for pre-calcination at a temperature of 890 ± 20 °C for 3 h;

[0073] (3) Ball milling: Pour the pre-calcined main component into a ball mill, and add auxiliary components (specific components and weight ratios are shown in Table 1), water, binder (polyvinyl alcohol), dispersant (ammonium citrate) and defoamer (n-octanol), and the mixing mass ratio of the main component, water, binder, dispersant and defoamer is 100:60:10:1:0.0015; during the feeding process, first perform low-speed ball milling at 50 rpm for 10 minutes, and then perform high-speed ball milling at 330 rpm for 1 hour; after the ball milling is completed, transfer the slurry to a stirring tank;

[0074] (4) Granulation: The slurry obtained by ball milling is sprayed and granulated into material particles with an average particle size of 100±50 μm in a spray tower;

[0075] (5) Molding: The material particles are pressed and molded to obtain a density of 3.20±0.05g / cm 3 H25mm×15mm×10mm annular blank;

[0076] (6) Sintering: Place the annular blank in a bell kiln and heat it to 650°C at a rate of 2.5°C / min in air atmosphere and keep it at that temperature for 5 h. Then heat it to 920°C at a rate of 1.3°C / min and keep it at that temperature for 3 h. Then cool it to 500°C at a rate of 4.3°C / min and finally cool it to 50°C at a rate of 6°C / min.

[0077] The surface microstructure of the sintered nickel-zinc ferrite material obtained in this embodiment is shown in FIG. Figure 1 .

[0078] Depend on Figure 1 It can be seen that the surface morphology of the sintered nickel-zinc ferrite material obtained in this embodiment is uniform and the grain size is uniform.

[0079] Example 2

[0080] This embodiment provides a nickel-zinc ferrite material and a preparation method thereof, the preparation method comprising the following steps:

[0081] (1) Ingredients: The main components were weighed according to the components and weight ratios shown in Table 1 and wet ball milled and spray granulated in sequence; wherein, during the wet ball milling, the mixing mass ratio of the main component, the grinding medium (a steel ball with a diameter of 5 mm) and water was 1:6.5:0.5, the ball milling time was 40 min, and the particle size distribution of the obtained slurry satisfied X50 of 0.5 μm and X90 of 1.5 μm;

[0082] (2) Pre-calcination: The material obtained by spray granulation is fed into a rotary kiln at a rate of 150 kg / h for pre-calcination at a temperature of 850 ± 20 °C for 3 h;

[0083] (3) Ball milling: Pour the pre-calcined main component into a ball mill, and add auxiliary components (specific components and weight ratios are shown in Table 1), water, binder (polyvinyl alcohol), dispersant (ammonium citrate) and defoamer (n-octanol), and the mixing mass ratio of the main component, water, binder, dispersant and defoamer is 100:60:10:0.6:0.001; during the feeding process, first perform low-speed ball milling at 40 rpm for 10 minutes, and then perform high-speed ball milling at 360 rpm for 2 hours; after the ball milling is completed, transfer the slurry to a stirring tank;

[0084] (4) Granulation: The slurry obtained by ball milling is sprayed and granulated into material particles with an average particle size of 100±50 μm in a spray tower;

[0085] (5) Molding: The material particles are pressed and molded to obtain a density of 3.20±0.05g / cm 3 H25mm×15mm×10mm annular blank;

[0086] (6) Sintering: Place the annular blank in a bell kiln and heat it to 650°C at 2.5°C / min in air atmosphere and keep it at that temperature for 4 h, then heat it to 1000°C at 1.3°C / min and keep it at that temperature for 2.5 h, then cool it to 600°C at 6°C / min, and finally cool it to 50°C at 7°C / min.

[0087] The surface microstructure of the sintered nickel-zinc ferrite material obtained in this embodiment is similar to that in Example 1, so it will not be described here.

[0088] Example 3

[0089] This embodiment provides a nickel-zinc ferrite material and a preparation method thereof, the preparation method comprising the following steps:

[0090] (1) Ingredients: The main components were weighed according to the components and weight ratios shown in Table 1 and wet ball milled and spray granulated in sequence; wherein, during the wet ball milling, the mixing mass ratio of the main component, the grinding medium (a steel ball with a diameter of 5 mm) and water was 1:5:0.8, the ball milling time was 40 min, and the particle size distribution of the obtained slurry satisfied X50 of 1.2 μm and X90 of 2 μm;

[0091] (2) Pre-calcination: The material obtained by spray granulation is fed into a rotary kiln at a rate of 150 kg / h for pre-calcination at a temperature of 890 ± 20 °C for 3 h;

[0092] (3) Ball milling: Pour the pre-calcined main component into a ball mill, and add auxiliary components (specific components and weight ratios are shown in Table 1), water, binder (polyvinyl alcohol), dispersant (ammonium citrate) and defoamer (n-octanol), and the mixing mass ratio of the main component, water, binder, dispersant and defoamer is 100:60:12:1.2:0.002; during the feeding process, first perform low-speed ball milling at 30 rpm for 10 minutes, and then perform high-speed ball milling at 300 rpm for 2 hours; after the ball milling is completed, transfer the slurry to a stirring tank;

[0093] (4) Granulation: The slurry obtained by ball milling is sprayed and granulated into material particles with an average particle size of 100±50 μm in a spray tower;

[0094] (5) Molding: The material particles are pressed and molded to obtain a density of 3.20±0.05g / cm 3 H25mm×15mm×10mm annular blank;

[0095] (6) Sintering: Place the annular blank in a bell kiln and heat it to 750°C at a rate of 2°C / min in an air atmosphere and keep it at that temperature for 5 h. Then heat it to 930°C at a rate of 3°C / min and keep it at that temperature for 5 h. Then cool it to 600°C at a rate of 4°C / min and finally cool it to 50°C at a rate of 6.5°C / min.

[0096] The surface microstructure of the sintered nickel-zinc ferrite material obtained in this embodiment is similar to that in Example 1, so it will not be described here.

[0097] Example 4

[0098] This embodiment provides a nickel-zinc ferrite material and a preparation method thereof, the preparation method comprising the following steps:

[0099] (1) Ingredients: The main components were weighed according to the components and weight ratios shown in Table 1 and wet ball milled and spray granulated in sequence; wherein, during the wet ball milling, the mixing mass ratio of the main component, the grinding medium (a steel ball with a diameter of 5 mm) and water was 1:4:0.5, the ball milling time was 60 min, and the particle size distribution of the obtained slurry satisfied X50 of 0.6 μm and X90 of 1.6 μm;

[0100] (2) Pre-calcination: The material obtained by spray granulation is fed into a rotary kiln at a rate of 150 kg / h for pre-calcination at a temperature of 930 ± 20 °C for 2 h;

[0101] (3) Ball milling: Pour the pre-calcined main component into a ball mill, and add auxiliary components (specific components and weight ratios are shown in Table 1), water, binder (polyvinyl alcohol), dispersant (ammonium citrate) and defoamer (n-octanol), and the mixing mass ratio of the main component, water, binder, dispersant and defoamer is 100:60:10:1:0.0015; during the feeding process, first perform low-speed ball milling at 20 rpm for 5 minutes, and then perform high-speed ball milling at 240 rpm for 2 hours; after the ball milling is completed, transfer the slurry to a stirring tank;

[0102] (4) Granulation: The slurry obtained by ball milling is sprayed and granulated into material particles with an average particle size of 100±50 μm in a spray tower;

[0103] (5) Molding: The material particles are pressed and molded to obtain a density of 3.20±0.05g / cm 3 H25mm×15mm×10mm annular blank;

[0104] (6) Sintering: Place the annular blank in a bell kiln and heat it to 750°C at a rate of 1.25°C / min in air atmosphere and keep it at that temperature for 2 h. Then heat it to 950°C at a rate of 1.6°C / min and keep it at that temperature for 2.5 h. Then cool it to 600°C at a rate of 4.7°C / min and finally cool it to 50°C at a rate of 7°C / min.

[0105] The surface microstructure of the sintered nickel-zinc ferrite material obtained in this embodiment is similar to that in Example 1, so it will not be described here.

[0106] Example 5

[0107] This embodiment provides a nickel-zinc ferrite material and a preparation method thereof, the preparation method comprising the following steps:

[0108] (1) Ingredients: The main components were weighed according to the components and weight ratios shown in Table 1 and wet ball milled and spray granulated in sequence; wherein, during the wet ball milling, the mixing mass ratio of the main component, the grinding medium (a steel ball with a diameter of 5 mm) and water was 1:6:1.1, the ball milling time was 20 min, and the particle size distribution of the obtained slurry satisfied X50 of 1 μm and X90 of 2 μm;

[0109] (2) Pre-calcination: The material obtained by spray granulation is fed into a rotary kiln at a rate of 150 kg / h for pre-calcination at a temperature of 930 ± 20 °C for 2 h;

[0110] (3) Ball milling: Pour the pre-calcined main component into a ball mill, and add auxiliary components (specific components and weight ratios are shown in Table 1), water, binder (polyvinyl alcohol), dispersant (ammonium citrate) and defoamer (n-octanol), and the mixing mass ratio of the main component, water, binder, dispersant and defoamer is 100:50:10:1:0.0025; during the feeding process, first perform low-speed ball milling at 60 rpm for 10 minutes, and then perform high-speed ball milling at 360 rpm for 2 hours; after the ball milling is completed, transfer the slurry to a stirring tank;

[0111] (4) Granulation: The slurry obtained by ball milling is sprayed and granulated into material particles with an average particle size of 100±50 μm in a spray tower;

[0112] (5) Molding: The material particles are pressed and molded to obtain a density of 3.20±0.05g / cm 3 H25mm×15mm×10mm annular blank;

[0113] (6) Sintering: Place the annular blank in a bell kiln and heat it to 550°C at a rate of 0.55°C / min in an air atmosphere and keep it at that temperature for 7 h. Then heat it to 880°C at a rate of 1.2°C / min and keep it at that temperature for 5 h. Then cool it to 600°C at a rate of 5°C / min and finally cool it to 50°C at a rate of 8°C / min.

[0114] The surface microstructure of the sintered nickel-zinc ferrite material obtained in this embodiment is similar to that in Example 1, so it will not be described here.

[0115] Example 6

[0116] This embodiment provides a nickel-zinc ferrite material and a preparation method thereof, the preparation method comprising the following steps:

[0117] (1) Ingredients: The main components were weighed according to the components and weight ratios shown in Table 1 and wet ball milled and spray granulated in sequence; wherein, during the wet ball milling, the mixing mass ratio of the main component, the grinding medium (a steel ball with a diameter of 5 mm) and water was 1:5:1, the ball milling time was 30 min, and the particle size distribution of the obtained slurry satisfied X50 of 1 μm and X90 of 2 μm;

[0118] (2) Pre-calcination: The material obtained by spray granulation is fed into a rotary kiln at a rate of 150 kg / h for pre-calcination at a temperature of 910 ± 20 °C for 2 h;

[0119] (3) Ball milling: Pour the pre-calcined main component into a ball mill, and add auxiliary components (specific components and weight ratios are shown in Table 1), water, binder (polyvinyl alcohol), dispersant (ammonium citrate) and defoamer (n-octanol), and the mixing mass ratio of the main component, water, binder, dispersant and defoamer is 100:60:10:0.1:0.0015; during the feeding process, the low speed ball milling at 50 rpm is first performed for 10 minutes, and then the high speed ball milling at 300 rpm is performed for 1.2 hours; after the ball milling is completed, the slurry is transferred to a stirring tank;

[0120] (4) Granulation: The slurry obtained by ball milling is sprayed and granulated into material particles with an average particle size of 100±50 μm in a spray tower;

[0121] (5) Molding: The material particles are pressed and molded to obtain a density of 3.20±0.05g / cm 3 H25mm×15mm×10mm annular blank;

[0122] (6) Sintering: Place the annular blank in a bell kiln and heat it to 600°C at a rate of 1.5°C / min and keep it at that temperature for 3 h in an air atmosphere, then heat it to 980°C at a rate of 2°C / min and keep it at that temperature for 3 h, then cool it to 600°C at a rate of 5.7°C / min, and finally cool it to 50°C at a rate of 6°C / min.

[0123] The surface microstructure of the sintered nickel-zinc ferrite material obtained in this embodiment is similar to that in Example 1, so it will not be described here.

[0124] Comparative Examples 1-11

[0125] Comparative Examples 1-11 respectively adopt the same preparation method as Example 1, the only difference is the specific proportion of the main component and the auxiliary component, see Table 1 below for details.

[0126] Table 1

[0127]

[0128]

[0129] The magnetic permeability μi, Curie temperature Tc and availability determination results of the nickel-zinc ferrite materials obtained in Examples 1-6 and Comparative Examples 1-11 at different temperatures are shown in Table 2 below.

[0130] Table 2

[0131]

[0132]

[0133] In the above table, the inductance of the sintered ring ferrite material is tested by Agilent E4991, and the magnetic permeability μi is calculated according to the size factor. The Curie temperature Tc and the magnetic permeability at various temperatures are tested by an LCR impedance meter and a high and low temperature controllable oven.

[0134] Note: The initial magnetic permeability μi of the nickel-zinc ferrite material obtained in Example 1-6 is 3000±25% (test conditions f=100kHz, u=0.1V), and the magnetic permeability at a high frequency of 300kHz is close to 2000, and the Q value exceeds 80.

[0135] Combining Table 1 and Table 2, it can be seen that: compared with Comparative Examples 1-11, when the specific proportions of the main components and the auxiliary components in Example 1-6 are controlled within a specific range, the obtained nickel-zinc ferrite material can simultaneously meet the requirements of high magnetic permeability and high Curie temperature within a wide temperature range, and has excellent comprehensive performance, which largely solves the application limitations of soft magnetic ferrite materials under extreme conditions.

[0136] It can be seen that the present invention optimizes and controls the ratio of the main components and the types and contents of the auxiliary components on the basis of the traditional nickel-zinc ferrite material. The obtained nickel-zinc ferrite material has a high initial magnetic permeability and a low temperature coefficient in a wide temperature range of -40 to 140°C, and the Curie temperature Tc is above 200°C. It has excellent comprehensive performance, solves the problem of low magnetic permeability of the material under different conditions, thereby improving the output stability of the inductor under extreme low temperature / high temperature conditions, and can be widely used in the fields of avionics, automotive electronics, and communication electronics.

[0137] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A nickel-zinc ferrite material, characterized in that: The nickel-zinc ferrite material is made of a main component and an auxiliary component; Based on the total weight of the main components, the main components include: 63.6-66.7wt% Fe2O3, 8.5-10.5wt% NiO, 16.5-18.4wt% ZnO and 7.6-8.5wt% CuO; Calculated by the total weight of the main components, the auxiliary components include: 600-3000 ppm of Bi2O3, 1500-2500 ppm of Co2O3 and 30-80 ppm of nano-SiO2.

2. A method for preparing the nickel-zinc ferrite material as claimed in claim 1, characterized in that: The preparation method comprises batching, pre-sintering, ball milling, granulation, molding and sintering in sequence.

3. The preparation method according to claim 2, characterized in that: The preparation comprises: weighing the main components according to the weight ratio and sequentially performing wet ball milling and spray granulation; Preferably, the mixing mass ratio of the main component, the grinding medium and the water during the wet ball milling process is 1:(4-8):(0.5-1.2); Preferably, the wet ball milling time is 20-60 min; Preferably, the particle size distribution of the slurry obtained by wet ball milling satisfies X50 of 0.5-1.2 μm and X90 of 1.5-2 μm.

4. The preparation method according to claim 2 or 3, characterized in that: The pre-firing is carried out in a rotary kiln; Preferably, the pre-burning temperature is 780-950°C; Preferably, the pre-burning time is 2-4 hours.

5. The preparation method according to any one of claims 2 to 4, characterized in that: The ball milling comprises: pouring the pre-burned main component into a ball mill, and adding auxiliary components, water, adhesive, dispersant and defoamer, and firstly performing low-speed ball milling and then high-speed ball milling during the feeding process; after the ball milling is completed, transferring the slurry to a stirring tank.

6. The preparation method according to claim 5, characterized in that: The mixing mass ratio of the main component, water, adhesive, dispersant and defoamer is 100:(40-150):(4-20):(0.1-2):(0.001-0.0025); Preferably, the rotation speed of the low-speed ball mill is 20-60 rpm; Preferably, the low-speed ball milling time is 5-10 min; Preferably, the high-speed ball milling speed is 240-360 rpm; Preferably, the high-speed ball milling time is 0.5-2h.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The granulation comprises spray granulation; Preferably, the average particle size of the particles obtained by the spray granulation is 30-200 μm; Preferably, the forming comprises press forming; Preferably, the press forming obtains an annular blank having a size of H (20-30) mm × (10-20) mm × (8-12) mm; Preferably, the density of the annular blank is 3.10-3.25 g / cm 3 .

8. The preparation method according to any one of claims 1 to 7, characterized in that: The sintering is carried out in a bell kiln; Preferably, the sintering comprises: firstly heating the temperature to a first temperature at a first rate and keeping the temperature for a first time, then heating the temperature to a second temperature at a second rate and keeping the temperature for a second time, then cooling the temperature to a third temperature at a third rate, and finally cooling the temperature to a fourth temperature at a fourth rate in an air atmosphere; Preferably, the first rate is 0.5-2.5°C / min; Preferably, the first temperature is 550-750°C; Preferably, the first time is 2-7h; Preferably, the second rate is 1-3°C / min; Preferably, the second temperature is 850-1000°C; Preferably, the second time is 2-5h; Preferably, the third rate is 4-7°C / min; Preferably, the third temperature is 500-700°C; Preferably, the fourth rate is 6-10°C / min; Preferably, the fourth temperature is 40-60°C.

9. The preparation method according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: (1) Preparation: Weigh the main components according to the weight ratio and perform wet ball milling and spray granulation in sequence; wherein, during the wet ball milling, the mixing mass ratio of the main component, the grinding medium and water is 1:(4-8):(0.5-1.2), the ball milling time is 20-60 min, and the particle size distribution of the obtained slurry satisfies X50 of 0.5-1.2 μm and X90 of 1.5-2 μm; (2) Pre-burning: The material obtained by spray granulation is placed in a rotary kiln for pre-burning at a temperature of 780-950°C for 2-4 hours; (3) ball milling: pour the pre-calcined main component into a ball mill, and add auxiliary components, water, adhesive, dispersant and defoamer, and the mixing mass ratio of the main component, water, adhesive, dispersant and defoamer is 100:(40-150):(4-20):(0.1-2):(0.001-0.0025); during the feeding process, first perform low-speed ball milling at 20-60rpm for 5-10min, and then perform high-speed ball milling at 240-360rpm for 0.5-2h; after the ball milling is completed, transfer the slurry to a stirring tank; (4) Granulation: The slurry obtained by ball milling is sprayed and granulated into material particles with an average particle size of 30-200 μm in a spray tower; (5) Molding: The material particles are pressed and molded to obtain a density of 3.10-3.25g / cm 3 H(20-30)mm×(10-20)mm×(8-12)mm annular blank; (6) Sintering: Place the annular blank in a bell kiln, first heat it to 550-750°C at 0.5-2.5°C / min in an air atmosphere and keep it at that temperature for 2-7h, then heat it to 850-1000°C at 1-3°C / min and keep it at that temperature for 2-5h, then cool it to 500-700°C at 4-7°C / min, and finally cool it to 40-60°C at 6-10°C / min.

10. An application of the nickel-zinc ferrite material as claimed in claim 1, characterized in that: The nickel-zinc ferrite material is used for preparing broadband transformers, filter inductors or laminated magnetic beads for electronic circuits.

Citation Information

Patent Citations

  • A low power consumption Mn-Zn ferrite magnetic material for ultra-high temperature condition and its making method

    CN101169996A

  • Nickel-zinc ferrite material, and preparation method and use thereof

    CN110357610A

  • Nickel-zinc high-permeability material with wide temperature range and low specific temperature coefficient and preparation method of nickel-zinc high-permeability material

    CN112079633A